Accelerating retreat and high-elevation thinning of glaciers in central Spitsbergen - Małecki, Jakub (My University, 2016)
Svalbard is a heavily glacier-covered archipelago in the Arctic. Dickson Land (DL), in the central part of the largest island, Spitsbergen, is relatively arid, and as a result, glaciers there are relatively small and restricted mostly to valleys and cirques. This study presents a comprehensive analysis of glacier changes in DL based on inventories compiled from topographic maps and digital elevation models for the Little Ice Age maximum (LIA), the 1960s, 1990 and 2009/11. Total glacier area decreased by ~38 % since the LIA maximum, and front retreat has increased over the study period. Recently, most of the local glaciers have been consistently thinning in all elevation bands, in contrast to larger Svalbard ice masses which remain closer to balance. The mean 1990–2009/11 geodetic mass balance of glaciers in DL is among the most negative from the Svalbard regional means known from the literature.
Keywords: glacier; Svalbard; mass balance; retreat; spitsbergen; Dickson Land; glaciology; elevation changes; melt